Constitutio Criminalis Theresiana - Some institutes of the general part of criminal procedure law - - Feješ, Ištvan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
Theresiana is little known code in Serbia, even although it is an important step in the development of criminal procedure law in the large part of Europe. Unil now we have shown the majority of substantive criminal law institutions. This paper is going to talk about the criminal - procedure provisions of the code. Due to the volume of the materia it was only possible to analyse some institutions, the intitutions of the so called general part of criminal procedure law.
Keywords: general part of the criminal procedure law; inquisitorial procedure; Theresiana